Strategic Planning and Institutional Development Plan: an overview of the academic production of brazilian Public Higher Education Institutions (Research, Society and Development, 2022)
The Public Higher Education Institutions (PHEIs) have the planning prepared through a model of Institutional Development Plan (IDP) proposed by the government as an instrument of institutional policy. In this scenario, the objective of this study is to understand the occurrence of Strategic Planning in PHEIs through the investigation of Theses and Dissertations that discussed about the Institutional Development Plan (IDP) and that are available in the database DLTD - Digital Library of Theses and Dissertations. This is a descriptive study with a qualitative approach. The Iramuteq software and the content analysis technique were used for analysis. It is concluded with this work that the IDP is approached as an instrument of management and public policies, presenting the PHEIs with difficulties in their development. For this reason, the academic papers portray the problems related to the phases of the IDP, giving preference to qualitative approaches and methods. It became evident that the IDPs are not always products of Strategic Planning and that the PHEIs demonstrate lack of strategic orientation, planning.